Prevention and control of tuberculosis in workplaces: how knowledgeable are the workers in Bangladesh? - Shafayetul Islam, Qazi; Akramul Islam, Md; Islam, Shayla; Masud Ahmed, Syed (© 2015 BioMed Central Ltd., 2017)
This article was published in BMC Public Health [© 2015 BioMed Central Ltd.] and the definite version is available at: http://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-015-2622-4